Staphylococcus lugdunensis : Genome sequence, genetic systems, virulence and an amplifiable isd locus - Heilbronner, Simon (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2013)
Staphylococcus lugdunensis is a coagulase negative staphylococcus (CoNS). Infections caused by CoNS are normally less severe than infections caused by S. aureus. However, S. lugdunensis is associated with a series of severe cases of infective endocarditis displaying an aggressive course of disease akin to S. aureus infections.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.